Chemoimmunotherapy as induction treatment in concurrent chemoradiotherapy for patients with nasopharyngeal carcinoma stage IVa - Kun-Peng Wu; Qing-Qing Li; Xu-Qiang Luo; Xiao-Xi Wang; Yan-Zhen Lai; Dan Tian; Hong-cheng Yang; Xue-Ling Wei; Lan-Ying Wang; Qiu-Ming Li; Dao Zhu; Si-Jie Chen; et al. (Annals of Medicine, 2025)
Background Chemoimmunotherapy is the first-line therapy for patients with recurrent or metastatic nasopharyngeal carcinoma (NPC) and is currently the main induction treatment option for patients with locoregionally advanced NPC. However, it remains unclear whether combining immunotherapy with standard induction chemotherapy enhances its efficacy. This study aimed to evaluate the efficacy, toxicity, and survival outcomes of induction chemoimmunotherapy in patients with locoregionally advanced NPC.Methods This study analyzed 50 patients with stage IVa NPC between January 2020 and December 2023 in our hospital. Among them, 23 received induction chemoimmunotherapy, and 27 received induction chemotherapy. All patients underwent standard platinum-based concurrent intensity-modulated radiation therapy. We compared tumor response and toxicity during induction treatment and concurrent chemoradiotherapy (CCRT) between the two groups.Results The objective and complete response rates were significantly higher in the induction chemoimmunotherapy group compared to the induction chemotherapy group (95.7% vs 77.8%, and 39.1% vs 22.2%, respectively). All patients completed radical CCRT. Median follow-up was 24 months. Patients who received induction chemoimmunotherapy had longer event-free survival (EFS) compared to those who received induction chemotherapy (p = 0.029, Hazard Ratio and 95%confidence interval [CI]: 0.24 [0.07–0.85]). The 24-month EFS was higher in the induction chemoimmunotherapy group compared with the chemotherapy group (24-month EFS rates and 95%CI: 88.9% [95%CI: 68.3%–100%] vs 62.6% [95%CI: 43.1%–82.1%]). No significant differences in adverse events were observed between the two groups during induction treatment and CCRT.Conclusions Adding immunotherapy to induction chemotherapy may be an effective and safe choice for treating patients with stage IVa NPC.